First records of Condylostylus depressus (Aldrich, 1901) and Condylostylus electus (Walker, 1852) (Diptera, Dolichopodidae) in coconut plantations in state of Pará, Brazil - Penner, Fernanda V.; Silva, Yorranna K. R. da; Soares, Matheus M. M.; Bastos, Lucas F.; Batista, Telma F. V. (Entomological Communications, 2021)
We record for the first time two species of Condylostylus Bigot, 1859 from Pará state, Brazil. Condylostylus depressus (Aldrich, 1901) and C. electus (Walker, 1852) were found on commercial crops of Cocos nucifera L., thus pointing to a possible value for biological control. In addition, we provide diagnoses and distributional maps for both species in Brazil.